El seguimiento del ciclo de vida de la mariposa Dione glycera (C. Felder and R. Felder 1861), una estrategia de aula para contextualizar y aplicar conceptos de Biología. (2012)
La investigación que se llevó a cabo buscó establecer una metodología educativa para los alumnos de grado octavo de la Institución Educativa de El Carmen del Municipio de Guasca. El diagnóstico que se realizó a los alumnos arrojó que estos presentan grandes deficiencias en conocimientos básicos de biología y ecología. A partir de ahí se formuló una propuesta pedagógica mediante el seguimiento del ciclo de vida de la mariposa Dione glycera para abordar algunos conceptos de la biología desde una perspectiva constructivista y de aprendizaje significativo. / The research conducted sought to establish an educational methodology for eighth grade students of School of the municipality of El Carmen Guasca. This methodology was based on a diagnosis that was made to students regarding their knowledge that they had about certain basic themes of natural science and ecology. The diagnosis was made students revealed that they have large gaps in knowledge as to what a cell, types of reproduction, concepts of the classification of living things and some basic concepts such as niche ecology and ecosystem. This diagnosis was established as an explanation for the lack of environmental sensitivity Middle students who have this particular course. From there it made a pedagogical approach of the biology of learning from a constructivist perspective and meaningful learning.